2007
DOI: 10.1161/hypertensionaha.107.091603
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming of Renal Glucocorticoid Sensitivity and the Renin-Angiotensin System

Abstract: Abstract-Fetal glucocorticoid excess leads to subsequent adult hypertension, but the mechanisms involved in this developmental programming remain largely unknown. In this study we tested the hypothesis that programmed hypertension in rats is linked to altered renal expression of the glucocorticoid receptor, mineralocorticoid receptor, and 11␤-hydroxysteroid dehydrogenase type 2 and components of the intrarenal and adipose renin-angiotensin system. The interactive effects of a postnatal diet enriched in omega-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 40 publications
5
71
0
4
Order By: Relevance
“…[2][3][4][5] Other studies in rodents and humans have shown that intrauterine environment can influence phenotype through its effect on epigenetic profile. [6][7][8][9] Rates of epigenetic fidelity through cell division are lower than those for genetic fidelity, with epimutation being one to Within-pair comparison of monozygotic (MZ) twins provides an ideal model for studying factors that regulate epigenetic profile, by controlling for genetic variation. Previous reports have demonstrated epigenetic variability within MZ pairs, but the contribution of early life exposures to this variation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Other studies in rodents and humans have shown that intrauterine environment can influence phenotype through its effect on epigenetic profile. [6][7][8][9] Rates of epigenetic fidelity through cell division are lower than those for genetic fidelity, with epimutation being one to Within-pair comparison of monozygotic (MZ) twins provides an ideal model for studying factors that regulate epigenetic profile, by controlling for genetic variation. Previous reports have demonstrated epigenetic variability within MZ pairs, but the contribution of early life exposures to this variation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we measured urinary levels of corticosterone and aldosterone and adrenal expression of key genes that promote adrenal steroidogenesis. The interactive effects of a postnatal, high-omega-3 fatty acid diet were also assessed because our previous studies show that this dietary intervention prevents several of the adverse phenotypic outcomes of maternal dexamethasone treatment (Wyrwoll et al 2006(Wyrwoll et al , 2007. It is not known, however, whether this beneficial effect of postnatal omega-3 fatty acid supplementation involves altered adrenal function.…”
Section: Introductionmentioning
confidence: 99%
“…GCs-exposed offspring has decreased 11 β-HSD 2 expression and increased GR expression as well as GR promoter hypomethylation in kidney (189). Cortisol will then exert mineralocorticoid activity through MR binding in kidney and resulted in sodium and water retention, hypokalaemia, low plasma renin and aldosterone concentrations, and eventually hypertension in adult life (190).…”
Section: Glucocorticoids Over Exposurementioning
confidence: 99%